The power of regret how looking backward moves us forward - Pink, Daniel H. (New York Riverhead Books, 2022)
Everybody has regrets, Daniel H. Pink explains in The Power of Regret. They?re a universal and healthy part of being human. And understanding how regret works can help us make smarter decisions, perform better at work and school, and bring greater meaning to our lives.
Includes bibliographical references and index.
Keywords: Regret